Myofunctional relation and orthodontic treatment in patient with Turner syndrome. Case report - Leiva, Noemi (2019)
The Turner Syndrome is a chromosome disorder produced by the total or partial absent of an X chromosome. The women who presents Turner syndrome can have a series of physical and functional alterations. The aim of this study is to present the case of a patient diagnosed with Turner syndrome, muscular hypotony and severe malocclusio treated with craneofacial muscular therapy combined with orthodontics at the Craneofacial Malformations Unit of the Faculty of Dentistry, University of Chile.